2021
DOI: 10.5551/jat.60624
|View full text |Cite
|
Sign up to set email alerts
|

Low Free Triiodothyronine Level as a Predictor of Cardiovascular Events and All-Cause Mortality in Patients Undergoing Hemodialysis: The DREAM Cohort

Abstract: Aim: Low T3 syndrome is characterized by low serum triiodothyronine (T3) levels without elevation of thyroid-stimulating hormone (TSH) in patients without apparent thyroid disease, which is known to be associated with worse clinical outcomes in various populations including those with kidney failure. In this study, we examined whether low free T3 (FT3) levels are independent predictor of cardiovascular disease (CVD) events in patients undergoing hemodialysis. Methods: This wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 34 publications
0
14
1
Order By: Relevance
“…Another study observed that low T3 is a powerful factor of mortality and low cardiac output in CABG patients (17). A recent Japanese study demonstrated low fT3 to be a predictor of MACE and all-cause mortality in hemodialysis patients (30). Multiple studies have reported low T3 levels to be a predictor of poor prognosis in acute and chronic heart failure (12,13,31,32).…”
Section: Discussionmentioning
confidence: 99%
“…Another study observed that low T3 is a powerful factor of mortality and low cardiac output in CABG patients (17). A recent Japanese study demonstrated low fT3 to be a predictor of MACE and all-cause mortality in hemodialysis patients (30). Multiple studies have reported low T3 levels to be a predictor of poor prognosis in acute and chronic heart failure (12,13,31,32).…”
Section: Discussionmentioning
confidence: 99%
“…Accepted for publication: August 10, 2021 Published online: September 11, 2021 was defined by 1) being treated with levothyroxine replacement (treated hypothyroidism) or 2) low free T4 ( 0.8 ng/dL) with high TSH ( 4.0 IU/L) 25) . No patients had central hypothyroidism (low free T4 with low TSH).…”
Section: Advance Publication Journal Of Atherosclerosis and Thrombosismentioning
confidence: 99%
“…The present study was conducted as a cross-sectional analysis of our prospective study cohort termed DREAM (Dialysis-Related Endocrine And Metabolic changes affecting cardiovascular disease) [11,16,17]. The total of 806 dialysis patients were treated at Inoue Hospital, Suita, Osaka, Japan, in December 2004.…”
Section: Selection Of Subjectsmentioning
confidence: 99%
“…Blood samples were drawn from the arteriovenous fistula just prior to an HD session at the beginning of the week, three days after the previous HD session, as previously reported [18]. Serum levels of FT3, FT4, and TSH were measured by specific chemiluminescent immunoassay (CLIA) methods performed by BIO MEDICAL LABORATORIES (BML, Inc., Tokyo, Japan), as previously described [11]. The reference ranges for FT3, FT4, and TSH were 2.2-4.1 pg/mL, 0.8-1.9 ng/dL, and 0.4-4.0 µIU/mL, respectively.…”
Section: Measurement Of Thyroid Hormones In Serummentioning
confidence: 99%
See 1 more Smart Citation